STRATEGI PEMERINTAH INDONESIA DALAM MENINGKATKAN EKSPOR KOPI KE AMERIKA SERIKAT - H. Hervinaldy; Den Yealta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study attempts to anything outline what are the government's strategies in increasing Indonesia's coffee exports to the United States as well as efforts to improve the quality of coffee and coffee farmers' prosperity. The research method used is qualitative research. This research is focused on discussing the government's efforts in increasing the export of coffee to the United States and the influence of farmers in increasing the exports. Secondly, the researcher felt it was necessary to give time limit to phenomenon or problem to be studied that is year 2000-2015.This study uses liberalist perspectives and interdepedensi theory and international cooperation theory. The level of analysis is international cooperation, as well as demand and supply.From the research results it is known that the export of Indonesian coffee to the United States fairly smoothly but behind the smooth exports of the welfare of coffee farmers is not guaranteed and coffee exports made by Indonesia mostly in the form of coffee beans.Keywords: Export, Coffee, Strategy, Enhancement,Government, Indonesia, USA